2021
DOI: 10.3390/jof7070538
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Relationships in the Toxin-Producing Fungal Endophyte, Alternaria oxytropis Using Polyketide Synthase and Non-Ribosomal Peptide Synthase Genes

Abstract: The legume Oxytropis sericea hosts a fungal endophyte, Alternaria oxytropis, which produces secondary metabolites (SM), including the toxin swainsonine. Polyketide synthase (PKS) and non-ribosomal peptide synthase (NRPS) enzymes are associated with biosynthesis of fungal SM. To better understand the origins of the SM, an unannotated genome of A. oxytropis was assessed for protein sequences similar to known PKS and NRPS enzymes of fungi. Contigs exhibiting identity with known genes were analyzed at nucleotide a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 53 publications
(74 reference statements)
0
4
0
Order By: Relevance
“…Secreted GHs of plant-associated fungi and oomycetes have been reported to act as effectors to promote microbial host colonization or activating the plant immune system [ 59 , 60 ]. In addition, Fusarium can produce abundant secondary metabolites, including polyketide and non-ribosomal peptide, which can directly damage the cells and tissues of host plants, breach plant defense barriers, and even suppress the immune system response, thereby promoting the development of disease [ 61 ]. The biosynthesis of these metabolites is often regulated by numerous genes such as CYP450 , PKS , NRPS , and others [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Secreted GHs of plant-associated fungi and oomycetes have been reported to act as effectors to promote microbial host colonization or activating the plant immune system [ 59 , 60 ]. In addition, Fusarium can produce abundant secondary metabolites, including polyketide and non-ribosomal peptide, which can directly damage the cells and tissues of host plants, breach plant defense barriers, and even suppress the immune system response, thereby promoting the development of disease [ 61 ]. The biosynthesis of these metabolites is often regulated by numerous genes such as CYP450 , PKS , NRPS , and others [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Post 24 h of treatment, MDA-MB-231 and MCF-7 cells were trypsinized and rinsed with cold 1X PBS, and 1 × 10 5 cells were resuspended in Annexin binding buffer. The resuspended cells were incubated with 5 μL of Annexin V-FITC and 1 μL of PI (100 μg/mL) at room temperature for 15 gloeosporioides in human breast cancer cells MDA-MB-231 and MCF-7 was evaluated using the 2′, 7′-dichlorofluorescein diacetate (H2DCFDA) dye-based assay as described previously. 30 Briefly, human breast cancer cells, MDA-MB-231 and MCF-7, at a density of 2 × 10 5 cells were treated with the EA extract of C. gloeosporioides with a respective IC 50 value for 24 h. The treated cells were harvested and homogenized in 1X PBS, followed by centrifugation at 10,000g at 4 °C.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Beside these, fungal endophytes are also known as a producer of enzymes including polyketide synthase (PKS) and non-ribosomal peptide synthase. Biosynthetic pathways of many fungal endophyte-derived bioactive compounds include crucial steps which are catalyzed by multifunctional PKS enzymes . A growing body of research has shown that bioactive compounds from well-known fungal genera like Fusarium , Alternaria , Curvularia , Aspergillus , Penicillium , Cladosporium , and Diaporthe significantly reduce the risk of cancer, cardiovascular disease, diabetes, and other conditions related to oxidative stress. , Besides these fungal species, the endophyte Colletotrichum gloeosporioides is also reported to be isolated from various plant tissues either in the form of a fungal endophyte or as a plant pathogen .…”
Section: Introductionmentioning
confidence: 99%
“…This study used RNAi for the rst time to silence the swnK gene, which gave similar effects to knockout of the gene on SW production in M. anisopliae. Creamer et al speci cally characterized the SWNK, NRPS, and SWNK/NRPS in A. oxytropis(Creamer et al 2021). Li and Holdom found that the growth rate of strain reaches the maximum between the rst day and the second day(Li et al 1995), which is consistent with the signi cant increase on the second day in the dry weight of mycelium measured in this experiment.Locoweed has a strong toxic effect on animals and has caused serious harm to the world's grassland animal husbandry(Tan et al.…”
mentioning
confidence: 99%